Effects of cultivation practices and hybrid selection on endofusariosis and mycotoxin contamination in maize - Kecskés, István; Pál, Károly; Pápai, Adrián; Bartók, Tibor; Horváth, Levente; Csótó, András (Acta Agraria Debreceniensis, 2025)
The aim of this study was to determine the levels of deoxynivalenol (DON) and fumonisin mycotoxins in tillage and no-till systems in 2020 and 2021. Additionally, we sought to establish the levels of internal Fusarium infection in different tillage systems. We examined four tillage systems for two years (conventional tillage (plowing), conservation tillage, reduced tillage, and strip-till). The results indicate that toxin levels varied between the two years, with fumonisin production dominant in 2021, while DON toxin production was dominant in 2020. Regarding internal Fusarium infection, the lowest levels were observed in the plowing system in 2020, whereas in 2021, the lowest levels were measured in the reduced tillage system. Like the low DON levels in 2020, the plowing-based tillage system resulted in the lowest fumonisin levels in 2021. Throughout our experiment, the toxin levels were below the permissible limits for unprocessed corn, with DON levels under 1750 μg kg-1 and combined fumonisin B1 and B2 levels under 4000 μg kg-1. However, in areas where toxin contamination is typically problematic, considering the beneficial impact of plowing on reducing toxin contamination might be advisable when planning tillage.